Toward circular and socially just urban mining in global societies and cities: Present state and future perspectives - Ghisellini, Patrizia; Ncube, Amos; Casazza, Marco; Passaro, Renato (Frontiers in Sustainable Cities, 2022)
This study evaluates the perspectives of urban mining in the framework of the circular economy (CE) and starts with a brief analysis of the size of global and urban metabolism and the role that plays materials and waste streams such as construction and demolition waste (C&DW) and waste from electronic and electrical equipment (WEEE). These can be considered as temporary stocks or deposits to be mined in the future, thus shedding light on the concept of recycling potential, end-of-life functional recycling, and material concentration. The recycling potential could be very variable as in the case of metals. The average concentration of some metals (e.g., gold) in WEEE shows that it is higher per ton of electronic product compared to the amount in mining ores. This explains the importance of the concept of urban mining in the circular economy (CE) transition, given that the CE concept was born to address the challenges of high resources consumption rates and worsening environmental problems. The urban mining phenomenon becomes timely and extremely important for cities as they are relevant hubs of materials and energy consumption and source of environmental and social impacts in external areas due to mining and extraction activities. This study points to the need for creating and establishing strong synergies between the concept of CE and urban mining and the role of cities as innovators in finding circular solutions by incorporating more socially just urban mining activities to improve urban resource management, land use, and local and global wellbeing.